Implementation of Criminal Sanctions for Domestic Violence (KDRT) in Indonesia - Samsidar Samsidar (PT. Anagata Sembagi Education, 2024)
Domestic violence (DV) is a form of human rights violation that has serious impacts on victims, especially women and children. In Indonesia, the crime of domestic violence is regulated in Law Number 23 of 2004 concerning the Elimination of Domestic Violence. This study aims to examine the extent to which the application of criminal sanctions against perpetrators of domestic violence is in accordance with the objectives of criminal law and provides effective protection to victims. Using a normative legal approach and supported by jurisprudence studies, this article reviews the effectiveness of law enforcement in the field, obstacles to law enforcement, and the need for a restorative approach. The results of the analysis show that although regulations have been comprehensively available, implementation at the law enforcement level still faces obstacles such as patriarchal culture, lack of understanding of the Domestic Violence Law, and minimal support for the victim protection system. This study recommends strengthening the capacity of law enforcement officers, public education, and optimizing the protection mechanism for victims of domestic violence. This study is expected to contribute to encouraging the renewal of criminal law policies that are more responsive to victims of domestic violence.